Implementation and effectiveness of advance care planning in hospitalized older adults with chronic heart failure: a mixed-methods systematic review and meta-analysis - Chen, Li; Cheng, Yuqiu; Qu, Jun; Wang, Zhangyi (Frontiers in Medicine, 2025)
ObjectivesThis study aims to integrate the data on the effects of a pre-established medical care program on hospitalized older adults with chronic heart failure (CHF).MethodA comprehensive systematic review incorporating mixed research methodologies was undertaken. Quality assessment was conducted using the Critical Appraisal Tool developed by Joanna Briggs Institute, adhering to the PRISMA guidelines for studies. Where appropriate, data were synthesized and aggregated for meta-analysis or meta-aggregation.ResultsA total of 2,825 articles were found, of which 11 met the inclusion criteria. Meta-analysis showed that the implementation of advance care planning (ACP) can significantly increase the willingness and proportion of patients with CHF to choose and receive hospice services during their end-of-life phase. Meta-aggregation showed that the ACP intervention has a positive impact on participants, promotes their knowledge and understanding, and makes them share their decision-making with their families.ConclusionACP is a promising and feasible intervention that can help older adults with CHF accurately understand ACP and express their wishes timely. This study provides insights and empirical evidence to improve ACP, and valuable guidance and reference for future clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO, identifier: CRD42024580814.